Preparation method and application of lithium-sulfur battery positive electrode material
By designing the multifunctional coupling of "limited domain-anchored-catalytic conversion" in the positive electrode material of lithium sulfur batteries, the chemical adsorption effect of three-dimensional porous biological carbon and N and P co-doped, combined with the In2O3 catalyst, the problem of LiPSs shuttle effect in lithium sulfur batteries is solved, significantly improving the rate performance and cycle stability of the battery.
Patent Information
- Application Number
- CN202411989219.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Lithium sulfur batteries have slow redox kinetics and rapid capacity attenuation due to the poor conductivity of elemental sulfur and the shuttle effect of lithium polysulfide, which hinders its commercialization progress.
Using structural design and multifunctional coupling, a lithium-sulfur battery catalytic material with multifunctional coupling function of "limited domain-anchored-catalytic conversion" is constructed. Through the physical domain confining effect of three-dimensional porous biological carbon, the chemoadsorption of N and P, and the loading of catalyst In2O3, the shuttle effect of LiPSs is inhibited.
It effectively inhibits the shuttle effect of LiPSs and significantly improves the rate performance and cycle stability of lithium-sulfur batteries.
Smart Images

Figure CN119400842B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-sulfur battery positive electrode materials, and in particular relates to a preparation method and application of a lithium-sulfur battery positive electrode material. Background Art
[0002] In the new generation of battery storage systems, lithium-sulfur batteries have the following outstanding advantages: mass energy density up to 2500Wh / kg and theoretical specific capacity of elemental sulfur up to 1675mAh / g. The mass energy density of lithium-sulfur batteries is 6 times that of lithium-ion batteries, and the volume energy density is 2 times that of lithium-ion batteries. Using lithium-sulfur batteries in new energy electric vehicles can achieve long-term endurance of electric vehicles while reducing battery mass, volume and cost. In addition, the active material sulfur cathode is safe, harmless, abundant in reserves and inexpensive.
[0003] However, due to the poor conductivity of elemental sulfur and the "shuttle effect" caused by soluble lithium polysulfides (LiPSs), lithium-sulfur batteries have slow redox kinetics and rapid capacity decay, which hinders their commercialization. By constructing a suitable sulfur carrier, the active material can be anchored on the carrier to inhibit the dissolution and shuttling of LiPSs. Among them, the carbon skeleton can alleviate the loss of active sulfur to a certain extent, but the inherent non-polar interface of the carbon material causes the force between it and the polar LiPSs to be relatively weak, making it difficult to effectively fix the active material, resulting in the inevitable shuttle effect and loss of active materials during the cycle. Polar compounds can anchor LiPSs through chemical bonding, thereby inhibiting their dissolution process, but most polar compounds have poor stability during the charge and discharge process, resulting in reduced cycle stability of lithium-sulfur batteries.
[0004] Patent document with application number CN2022117269626 discloses a method for preparing a lithium-sulfur battery catalyst material, which is used to prepare a lithium-sulfur battery catalyst material in which atomically dispersed Ni-Co bimetallic tandem sites are coordinated with nitrogen and embedded in porous carbon. Zn(NO3)2·6H2O, Co(NO3)2·6H2O and Ni(NO3)2·6H2O are dissolved in methanol to form a mixed solution, 2-methylimidazole and methanol are added to the mixed solution and the solution is aged after stirring, and then the precipitate is collected by filtration. The precipitate is washed and vacuum-dried to obtain ZnCoNi-ZIF; the ZnCoNi-ZIF is then placed in a tubular furnace and heated to obtain a pyrolysis product, and the metal particles on the surface of the pyrolysis product are selectively removed after soaking treatment, and then vacuum-dried to obtain a lithium-sulfur battery catalyst material CoNi-NC. The prepared lithium-sulfur battery catalyst material CoNi-NC can be used to prepare a sulfur-based composite material CoNi-NC-S for use as a positive electrode of a lithium-sulfur battery, which can effectively improve the rate performance of the lithium-sulfur battery and has good cycle stability. However, the technical solution of this patent document does not fundamentally solve the shuttle effect of LiPSs.
[0005] In view of this, the present invention designs the microstructure of the positive electrode material of the lithium-sulfur battery to solve the poor conductivity of elemental sulfur and the "shuttle effect" of LiPSs, thereby effectively improving its rate performance and cycle stability. Summary of the invention
[0006] The technical problem solved by the present invention is to provide a method for preparing a lithium-sulfur battery positive electrode material with a simple process, environmental friendliness and large-scale production. The method adopts structural design and multifunctional coupling to construct a lithium-sulfur battery positive electrode material with a multifunctional coupling effect of "confinement-anchoring-catalytic conversion". The physical confinement effect of three-dimensional porous biocarbon is used to suppress the shuttle effect of LiPSs in the positive electrode material, and the chemical adsorption of N and P is used to anchor LiPSs. At the same time, the catalyst In2O3 is loaded into the three-dimensional carbon conductive network to ensure that its role as a catalytic site is exposed to the greatest extent. The lithium-sulfur battery positive electrode material prepared by the present invention can achieve confinement and anchoring of LiPSs and promote their catalytic conversion, fundamentally suppress the shuttle effect of LiPSs and significantly improve their rate performance and cycle stability. Therefore, the lithium-sulfur battery positive electrode material can be used to prepare lithium-sulfur battery positive electrodes and further assembled into lithium-sulfur batteries.
[0007] The present invention adopts the following technical solution to solve the above technical problems: a method for preparing a positive electrode material for a lithium-sulfur battery, wherein the specific preparation steps are as follows:
[0008] Step S1: Preparation of porous biocarbon aerogel
[0009] Dispersing chitosan in deionized water to obtain a chitosan solution with a concentration of 3wt% to 5wt%, stirring the chitosan solution in a water bath at 20 to 40°C for 1 to 3h, then adding a crosslinking agent phytic acid solution dropwise to carry out a crosslinking reaction, stopping heating and stirring after observing that chitosan and phytic acid are completely crosslinked and condensed, allowing the reaction product to stand at room temperature and then packing it into a mold, then placing it in liquid nitrogen for 5 to 20s to achieve rapid freezing, and freeze-drying after observing that the reaction product is completely frozen to obtain a porous biocarbon aerogel;
[0010] Step S2: Preparation of porous biocarbon aerogel@In2O3 composites
[0011] The nano-In2O3 catalyst and anhydrous ethanol are uniformly mixed to obtain an In2O3 solution, and the porous biocarbon aerogel obtained in step S1 is immersed in the In2O3 solution, subjected to ultrasonic treatment for 1 to 3 hours, and then heated until the anhydrous ethanol is volatilized, and then freeze-dried to obtain a porous biocarbon aerogel@In2O3 composite material;
[0012] Step S3: Preparation of N, P co-doped porous biocarbon@In2O3 composite material
[0013] The porous biocarbon aerogel@In2O3 composite material obtained in step S2 is subjected to microwave heating treatment to carbonize the aerogel inside to obtain a N, P co-doped porous biocarbon@In2O3 composite material with a three-dimensional structure, wherein the power of the microwave heating treatment is 300-650W and the time is 2-8min;
[0014] Step S4: Preparation of N and P co-doped porous biocarbon@In2O3@S composite materials
[0015] The N, P co-doped porous biocarbon@In2O3 composite material obtained in step S3 is evenly mixed with elemental sulfur, and the mixed material is then transferred to a tubular furnace and calcined at 150-160° C. for 4-8 hours in an oxygen-free atmosphere to finally obtain a N, P co-doped porous biocarbon@In2O3@S composite material, i.e., a lithium-sulfur battery positive electrode material.
[0016] It is further defined that the concentration of phytic acid in the cross-linking agent phytic acid solution in step S1 is 0.5-1.2 mol / L.
[0017] It is further defined that the feeding ratio of chitosan and phytic acid in step S1 is 1g:0.5-3mL
[0018] It is further defined that the freeze-drying temperature in step S1 is -80°C to -50°C, and the time is 8 to 72 hours.
[0019] It is further defined that the mass ratio of the nano-In2O3 catalyst to the porous biocarbon aerogel in step S2 is 0.5 to 3:1.
[0020] It is further defined that the freeze-drying temperature in step S2 is -80°C to -50°C, and the time is 8 to 48 hours.
[0021] It is further defined that the mass ratio of the N and P co-doped porous biocarbon@In2O3 composite material to elemental sulfur in step S4 is 3:5-10.
[0022] The application of the lithium-sulfur battery positive electrode material prepared based on the above method in the preparation of lithium-sulfur battery positive electrode.
[0023] The lithium-sulfur battery positive electrode prepared based on the above method is used to assemble a lithium-sulfur battery.
[0024] Compared with the prior art, the present invention has the following technical advantages and beneficial effects:
[0025] 1. The cross-linking agent phytic acid used in the preparation process of the positive electrode material of the lithium-sulfur battery of the present invention is a green, non-toxic, environmentally friendly compound that can be widely extracted from plants. The hydroxyl group and the six phosphate groups (PO4 3- ) can cross-link with the amino and hydroxyl groups in chitosan to form a three-dimensional network structure. The three-dimensional porous biochar formed by carbonization can improve the conductivity of elemental sulfur and physically confine LiPSs, thereby inhibiting its "shuttle effect". In addition, during the microwave carbonization process, the decomposition of some oxygen-containing groups in phytic acid and the discharge of some volatile gases play a role in forming pores in the porous biochar, increasing the specific surface area of the carbon material and further improving the physical confinement effect on LiPSs.
[0026] 2. The phosphate groups and inositol molecules in phytic acid can enhance the chemical anchoring effect on LiPSs by P doping the prepared carbon materials during microwave carbonization. Furthermore, the amino groups in chitosan can achieve N doping of the prepared carbon materials during microwave carbonization. Therefore, the porous biochar prepared by chitosan and phytic acid contains abundant N and P doping sites, which can enhance its chemical anchoring effect on LiPSs. In addition, the introduction of phosphorus-containing groups in the cross-linking agent phytic acid can effectively regulate the surface electronic structure of carbon materials, enhance the adsorption of materials on LiPSs and the wettability of electrolytes, thereby improving the utilization rate of sulfur and cycle stability. The N and P co-doped porous biocarbon carrier prepared by chitosan and phytic acid uses the constructed three-dimensional carbon conductive network to physically confine LiPSs. At the same time, the chemical adsorption of N and P co-doped sites is used to anchor LiPSs, thereby using the "confinement-anchoring" effect to inhibit the shuttle effect of LiPSs.
[0027] 3. The In-based catalyst (nano-In2O3) used in the preparation process of the positive electrode material of the lithium-sulfur battery of the present invention can selectively reduce the solid-liquid (S8 is reduced to LiPSs) conversion rate, and accelerate the liquid-solid (LiPSs is reduced to Li2S) conversion rate, thereby reducing the accumulation of LiPSs in the electrolyte, and then inhibiting the shuttle effect. The present invention loads a nano-In2O3 catalyst with selective catalytic effect into the porous biochar, which reduces the rate of reduction of S element to LiPSs, and accelerates the conversion of LiPSs to the discharge product Li2S. In addition, the formation of the catalytic intermediate LiInS2 changes the reaction path of LiPSs, thereby reducing the accumulation of LiPSs in the electrolyte, improving the utilization rate of sulfur active substances, and effectively inhibiting the shuttle effect.
[0028] 4. The three-dimensional porous biocarbon formed by microwave carbonization in the preparation process of the positive electrode material of the lithium-sulfur battery of the present invention can be used as a host material of S due to its excellent conductivity, large specific surface area and high porosity. It can not only physically limit the shuttle effect of LiPSs and alleviate the volume expansion problem of the sulfur electrode during charging and discharging, but also effectively promote the transmission of electrons and the diffusion of lithium ions. The N and P co-doped carbon framework anchors LiPSs by chemical bonding, alleviates its diffusion and shuttling between electrodes, so as to improve the utilization rate of S and cycle stability. Therefore, the N and P co-doped porous biocarbon @ In2O3 @ S composite material prepared by the present invention suppresses the shuttle effect of LiPSs by virtue of the physical confinement effect of its three-dimensional porous biocarbon, and anchors LiPSs by the chemical adsorption of N and P. At the same time, the catalyst nano-In2O3 is loaded into the three-dimensional carbon conductive network to ensure that its role as a catalytic site is exposed to the greatest extent. This lithium-sulfur battery positive electrode material with the multifunctional coupling effect of "confinement-anchoring-catalytic conversion" can effectively confine and anchor LiPSs and promote their catalytic conversion, fundamentally inhibiting the shuttle effect of LiPSs and significantly improving their rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a mechanism diagram of the present invention for achieving the “confinement-anchoring-catalytic conversion” of LiPSs.
[0030] Figure 2 is a SEM image of the porous biochar in Example 1.
[0031] Figure 3 It is a comparison chart of the rate charge and discharge performance of lithium-sulfur batteries assembled with the positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4. DETAILED DESCRIPTION
[0032] The present invention suppresses the shuttle effect of LiPSs by constructing N and P co-doped porous biocarbon@In2O3@S composite materials, solves the poor conductivity of S, and further improves its electrochemical performance.
[0033] The present invention specifically prepares the positive electrode material of a lithium-sulfur battery by the following method, comprising the following steps:
[0034] Step S1: Preparation of porous biocarbon aerogel
[0035] Disperse chitosan in an appropriate amount of deionized water to prepare a chitosan solution of a certain concentration (optionally 3wt% to 5wt%); after ultrasonic dispersion, stir with a magnetic stirrer for 1 to 3 hours in a water bath at 20 to 40°C; add a certain concentration of cross-linking agent (optionally phytic acid) dropwise for cross-linking reaction (the feed ratio of chitosan to phytic acid can be 1g:0.5 to 3mL, and the concentration of the phytic acid solution can be 0.5 to 1.2 mol / L), and stop heating and stirring after observing that chitosan and phytic acid are completely cross-linked and condensed; slowly dispense it into a mold after standing at room temperature to avoid bubbles during the dispensing process; then, quickly freeze it (optionally place it in liquid nitrogen for 5 to 20s), and freeze-dry it after observing that it is completely frozen (the freeze-drying temperature can be -80 to -50°C and the time can be 8 to 72h) to obtain a porous biocarbon aerogel.
[0036] Water has the phenomenon of unidirectional condensation under an asymmetric cold source, and an ice crystal structure will be formed on the cold side and will grow along the temperature gradient. Therefore, after chitosan and phytic acid are cross-linked, the mixed solution with deionized water will be cooled on one side. Driven by the growth of ice crystals, chitosan and phytic acid will accumulate between the ice crystals, and then be molded into a cylindrical structure after being freeze-dried. After that, the ice evaporates in gaseous form to form porous biocarbon aerogel.
[0037] Step S2: Preparation of porous biocarbon aerogel@In2O3 composites
[0038] The nano-In2O3 catalyst and the porous biocarbon aerogel obtained in step S1 are weighed in a certain mass ratio (optionally 0.5 to 3:1). The nano-In2O3 and anhydrous ethanol are mixed evenly to obtain an In2O3 solution, and the porous biocarbon aerogel is immersed in the evenly mixed In2O3 solution, and then heated to evaporate the anhydrous ethanol after ultrasonic treatment for 1 to 3 hours. Freeze-drying (the freeze-drying temperature can be -80 to -50°C and the time can be 8 to 48 hours) is performed to obtain a porous biocarbon aerogel@In2O3 composite material.
[0039] (3) Preparation of N and P co-doped porous biocarbon@In2O3 composites
[0040] The porous biocarbon aerogel@In2O3 composite material obtained in step S2 is subjected to microwave heating treatment (the power can be selected to be 300-650W and the time is 2-8min) to carbonize the aerogel inside it to obtain a N, P co-doped porous biocarbon@In2O3 composite material with a three-dimensional structure.
[0041] (4) Preparation of N and P co-doped porous biocarbon@In2O3@S composites
[0042] The N, P co-doped porous biocarbon@In2O3 composite material obtained in step S3 and elemental sulfur are mixed uniformly in a certain mass ratio (optionally 3:5-10), and then the mixed material is transferred to a tubular furnace, and calcined (the calcination temperature can be 150-160°C and the insulation time can be 4-8h) under an oxygen-free atmosphere (optionally nitrogen protection) to obtain the N, P co-doped porous biocarbon@In2O3@S composite material, i.e., the positive electrode material of a lithium-sulfur battery.
[0043] The positive electrode material prepared by the above method can be further applied to lithium-sulfur batteries. Specifically, it is used as a battery positive electrode material to prepare a lithium-sulfur battery positive electrode and further used to assemble a lithium-sulfur battery.
[0044] In order to better illustrate the above technical solution, the above technical solution will be described in detail below in conjunction with specific embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies implemented based on the above content of the present invention belong to the scope of the present invention.
[0045] Example 1
[0046] Step S1: Porous biocarbon aerogel preparation
[0047] Disperse 24g chitosan powder in 588mL deionized water to prepare a chitosan solution with a concentration of 4wt%; after ultrasonic dispersion, stir with a magnetic stirrer in a 30℃ water bath for 2h. Add 36mL of phytic acid with a concentration of 1.05mol / L as a crosslinking agent for crosslinking reaction, and stop heating and stirring after observing that chitosan and phytic acid are completely crosslinked and condensed; slowly dispense it into a mold after standing at room temperature to avoid bubbles during the dispensing process; then place it in liquid nitrogen for 10s for rapid freezing, and freeze-dry it at -70℃ for 48h after observing complete freezing, so as to obtain porous biocarbon aerogel.
[0048] Step S2: Preparation of porous biocarbon aerogel@In2O3 composites
[0049] According to the mass ratio of nano-In2O3 catalyst to porous biocarbon aerogel of 1.5:1, the materials were weighed separately, 600 mg of nano-In2O3 was weighed and mixed evenly with anhydrous ethanol to obtain an In2O3 solution. After being evenly mixed, 400 mg of the porous biocarbon aerogel obtained in step S1 was weighed and immersed in the In2O3 solution, and then ultrasonicated for 2 hours and then heated until the anhydrous ethanol volatilized, and then freeze-dried at -70°C for 24 hours to obtain a porous biocarbon aerogel@In2O3 composite material.
[0050] Step S3: Preparation of N, P co-doped porous biocarbon@In2O3 composite material
[0051] The porous biocarbon aerogel@In2O3 composite material obtained in step S2 was subjected to microwave heating treatment at a power of 500 W for 6 minutes to carbonize the aerogel inside the composite material to obtain a N, P co-doped porous biocarbon@In2O3 composite material with a three-dimensional structure.
[0052] Step S4: Preparation of N and P co-doped porous biocarbon@In2O3@S composite materials
[0053] The N, P co-doped porous biocarbon@In2O3 and elemental sulfur in step S3 are evenly mixed in a mass ratio of 3:7, and then the mixed material is transferred to a tubular furnace and calcined at 155°C for 6 hours under nitrogen protection to finally obtain a N, P co-doped porous biocarbon@In2O3@S composite material, which is a lithium-sulfur battery positive electrode material.
[0054] Example 2
[0055] Step S1: Porous biocarbon aerogel preparation
[0056] Disperse 24g chitosan powder in 800mL deionized water to prepare a chitosan solution with a concentration of 3wt%; after ultrasonic dispersion, stir with a magnetic stirrer in a 20℃ water bath for 1h. Add 12mL of phytic acid with a concentration of 0.5mol / L as a crosslinking agent for crosslinking reaction, and stop heating and stirring after observing that chitosan and phytic acid are completely crosslinked and condensed; slowly dispense it into a mold after standing at room temperature to avoid bubbles during the dispensing process; then place it in liquid nitrogen for 5s for rapid freezing, and freeze-dry it at -80℃ for 8h after observing complete freezing, so as to obtain porous biocarbon aerogel.
[0057] Step S2: Preparation of porous biocarbon aerogel@In2O3 composites
[0058] According to the mass ratio of nano-In2O3 catalyst to porous biocarbon aerogel of 0.5:1, the materials were weighed separately, 600 mg of nano-In2O3 was weighed and mixed evenly with anhydrous ethanol to obtain an In2O3 solution. After being evenly mixed, 1200 mg of the porous biocarbon aerogel obtained in step S1 was weighed and immersed in the In2O3 solution, and then ultrasonicated for 1 hour and heated until the anhydrous ethanol evaporated, and then freeze-dried at -80°C for 8 hours to obtain a porous biocarbon aerogel@In2O3 composite material.
[0059] Step S3: Preparation of N, P co-doped porous biocarbon@In2O3 composite material
[0060] The porous biocarbon aerogel@In2O3 composite material obtained in step S2 was subjected to microwave heating treatment at a power of 300 W for 2 min to carbonize the aerogel inside the composite material to obtain a N, P co-doped porous biocarbon@In2O3 composite material with a three-dimensional structure.
[0061] Step S4: Preparation of N and P co-doped porous biocarbon@In2O3@S composite materials
[0062] The N, P co-doped porous biocarbon@In2O3 composite material obtained in step S3 and elemental sulfur are evenly mixed in a mass ratio of 3:5, and then the mixed material is transferred to a tubular furnace and calcined at 150°C for 4 hours under nitrogen protection to obtain the N, P co-doped porous biocarbon@In2O3@S composite material, which is the positive electrode material of the lithium-sulfur battery.
[0063] Example 3
[0064] Step S1: Porous biocarbon aerogel preparation
[0065] Disperse 24g chitosan powder in 456mL deionized water to prepare a chitosan solution with a concentration of 5wt%; after ultrasonic dispersion, stir with a magnetic stirrer in a 40℃ water bath for 3h. Add 72mL of phytic acid with a concentration of 1.2mol / L as a crosslinking agent for crosslinking reaction, and stop heating and stirring after observing that chitosan and phytic acid are completely crosslinked and condensed; slowly dispense it into a mold after standing at room temperature to avoid bubbles during the dispensing process; then place it in liquid nitrogen for 20s for rapid freezing, and freeze-dry it at -50℃ for 72h after observing complete freezing, so as to obtain porous biocarbon aerogel.
[0066] Step S2: Preparation of porous biocarbon aerogel@In2O3 composites
[0067] The raw materials were weighed according to the mass ratio of nano-In2O3 catalyst to porous biocarbon aerogel of 3:1, and 600 mg of nano-In2O3 was weighed and mixed with anhydrous ethanol to obtain an In2O3 solution. After being mixed evenly, 200 mg of the porous biocarbon aerogel obtained in step S1 was weighed and immersed in the In2O3 solution, and then heated until the anhydrous ethanol was volatilized after ultrasonic treatment for 3 hours. Then, it was freeze-dried at -50°C for 48 hours to obtain a porous biocarbon aerogel@In2O3 composite material.
[0068] Step S3: Preparation of N, P co-doped porous biocarbon@In2O3 composite material
[0069] The porous biocarbon aerogel@In2O3 composite material in step S2 was subjected to microwave heating treatment at a power of 650 W for 8 minutes to carbonize the aerogel inside the composite material to obtain a N, P co-doped porous biocarbon@In2O3 composite material with a three-dimensional structure.
[0070] Step S4: Preparation of N and P co-doped porous biocarbon@In2O3@S composite materials
[0071] The N, P co-doped porous biocarbon@In2O3 and elemental sulfur obtained in step S3 are evenly mixed in a mass ratio of 3:10, and then the mixed material is transferred to a tubular furnace and calcined at 160°C for 8h under nitrogen protection to obtain a N, P co-doped porous biocarbon@In2O3@S composite material, i.e., a lithium-sulfur battery positive electrode material.
[0072] Comparative Example 1 (crosslinking agent is ordinary acetic acid)
[0073] Step S1: Porous biocarbon aerogel preparation
[0074] 24g chitosan powder was dispersed in 588mL deionized water to prepare a chitosan solution with a concentration of 4wt%. After uniform ultrasonic dispersion, a magnetic stirrer was used to stir for 2h in a 30℃ water bath. 36mL of 1.05mol / L crosslinking agent acetic acid was added to carry out a crosslinking reaction. After the chitosan and acetic acid were observed to be completely crosslinked and condensed, heating and stirring were stopped. After standing at room temperature, it was slowly dispensed into a mold to avoid bubbles during the dispensing process. After that, it was placed in liquid nitrogen for 10s for rapid freezing. After being observed to be completely frozen, it was freeze-dried at -70℃ for 48h to obtain a porous biocarbon aerogel.
[0075] Step S2: Preparation of porous biocarbon aerogel@In2O3 composites
[0076] The raw materials were weighed according to the mass ratio of nano-In2O3 catalyst to porous biocarbon aerogel of 1.5:1. 600 mg of nano-In2O3 was weighed and mixed with anhydrous ethanol to obtain an In2O3 solution. After being mixed evenly, 400 mg of the porous biocarbon aerogel obtained in step S1 was weighed and immersed in the In2O3 solution. After ultrasonic treatment for 2 hours, it was heated until the anhydrous ethanol volatilized, and then freeze-dried at -70°C for 24 hours to obtain a porous biocarbon aerogel@In2O3 composite material.
[0077] Step S3: Preparation of N-doped porous biocarbon@In2O3 composites
[0078] The porous biocarbon aerogel@In2O3 composite material obtained in step S2 was subjected to microwave heating treatment at a power of 500 W for 6 min to carbonize the aerogel inside the composite material to obtain an N-doped porous biocarbon@In2O3 composite material with a three-dimensional structure.
[0079] Step S4: Preparation of N-doped porous biocarbon@In2O3@S composites
[0080] The N-doped porous biocarbon@In2O3 composite material obtained in step S3 and elemental sulfur are evenly mixed in a mass ratio of 3:7, then transferred to a tubular furnace, and calcined at 155°C for 6 hours under nitrogen protection to finally obtain an N-doped porous biocarbon@In2O3@S composite material.
[0081] Comparative Example 2 (No selective catalyst nano-In2O3 added)
[0082] Step S1: Porous biocarbon aerogel preparation
[0083] Disperse 24g chitosan powder in 588mL deionized water to prepare a chitosan solution with a concentration of 4wt%; after ultrasonic dispersion, stir with a magnetic stirrer in a 30℃ water bath for 2h. Add 36mL of phytic acid with a concentration of 1.05mol / L as a crosslinking agent for crosslinking reaction, and stop heating and stirring after observing that chitosan and phytic acid are completely crosslinked and condensed; slowly dispense it into a mold after standing at room temperature to avoid bubbles during the dispensing process; then place it in liquid nitrogen for 10s for rapid freezing, and freeze-dry it at -70℃ for 48h after observing complete freezing, so as to obtain porous biocarbon aerogel.
[0084] Step S2: Preparation of N and P co-doped porous biocarbon
[0085] The porous biocarbon aerogel obtained in step S1 was subjected to microwave heating treatment at a power of 500 W for 6 minutes to carbonize the aerogel inside the aerogel to obtain N, P co-doped porous biocarbon with a three-dimensional structure.
[0086] Step S3: Preparation of N and P co-doped porous biocarbon@S composite materials
[0087] The N, P co-doped porous biochar and elemental sulfur obtained in step S2 were uniformly mixed in a mass ratio of 3:7, and then the mixture was transferred to a tubular furnace and calcined at 155°C for 6 hours under nitrogen protection to finally obtain a N, P co-doped porous biochar@S composite material.
[0088] Comparative Example 3 (Changing microwave heating to ordinary tube furnace sintering)
[0089] Step S1: Porous biocarbon aerogel preparation
[0090] Disperse 24g chitosan powder in 588mL deionized water to prepare a chitosan solution with a concentration of 4wt%; after ultrasonic dispersion, stir with a magnetic stirrer in a 30℃ water bath for 2h. Add 36mL of phytic acid with a concentration of 1.05mol / L as a crosslinking agent for crosslinking reaction, and stop heating and stirring after observing that chitosan and phytic acid are completely crosslinked and condensed; slowly dispense it into a mold after standing at room temperature to avoid bubbles during the dispensing process; then place it in liquid nitrogen for 10s for rapid freezing, and freeze-dry it at -70℃ for 48h after observing complete freezing, so as to obtain porous biocarbon aerogel.
[0091] Step S2: Preparation of porous biocarbon aerogel@In2O3 composites
[0092] The raw materials were weighed according to the mass ratio of nano-In2O3 catalyst to porous biocarbon aerogel of 1.5:1, and 600 mg of nano-In2O3 was weighed and mixed evenly with anhydrous ethanol to obtain an In2O3 solution. After being evenly mixed, 400 mg of the porous biocarbon aerogel obtained in step S1 was weighed and immersed in the In2O3 solution, and then ultrasonicated for 2 hours and heated until the anhydrous ethanol volatilized, and then freeze-dried at -70°C for 24 hours to obtain a porous biocarbon aerogel@In2O3 composite material.
[0093] Step S3: Preparation of N, P co-doped porous biocarbon@In2O3 composite material
[0094] The porous biocarbon aerogel@In2O3 composite material obtained in step S2 was transferred to a tubular furnace and calcined at 600°C for 2h in a nitrogen atmosphere to obtain a N, P co-doped porous biocarbon@In2O3 composite material with a three-dimensional structure.
[0095] Step S3: Preparation of N and P co-doped porous biocarbon@In2O3@S composite materials
[0096] The N, P co-doped porous biocarbon@In2O3 composite material obtained in step S3 and elemental sulfur are evenly mixed in a mass ratio of 3:7, and then the mixed material is transferred to a tubular furnace and calcined at 155°C for 6 hours under nitrogen protection to finally obtain a N, P co-doped porous biocarbon@In2O3@S composite material.
[0097] Comparative Example 4 (without rapid freezing)
[0098] Step S1: Porous biocarbon aerogel preparation
[0099] 24g chitosan powder was dispersed in 588mL deionized water to prepare a chitosan solution with a concentration of 4wt%. After uniform ultrasonic dispersion, a magnetic stirrer was used to stir for 2h in a 30℃ water bath. 36mL of phytic acid with a concentration of 1.05mol / L was added to carry out a crosslinking reaction. After observing that the chitosan and phytic acid were completely crosslinked and condensed, the heating and stirring were stopped. After standing at room temperature, the solution was slowly dispensed into a mold to avoid bubbles during the dispensing process. After that, the solution was freeze-dried at -70℃ for 48h to obtain a porous biocarbon aerogel.
[0100] Step S2: Preparation of porous biocarbon aerogel@In2O3 composites
[0101] According to the mass ratio of nano-In2O3 catalyst to porous biocarbon aerogel of 1.5:1, the materials were weighed separately, 600 mg of nano-In2O3 was weighed and mixed evenly with anhydrous ethanol to obtain an In2O3 solution. After being evenly mixed, 400 mg of the porous biocarbon aerogel obtained in step S1 was weighed and immersed in the In2O3 solution, and then ultrasonicated for 2 hours and then heated until the anhydrous ethanol volatilized, and then freeze-dried at -70°C for 24 hours to obtain a porous biocarbon aerogel@In2O3 composite material.
[0102] Step S3: Preparation of N, P co-doped porous biocarbon@In2O3 composite material
[0103] The porous biocarbon aerogel@In2O3 composite material obtained in step S2 was subjected to microwave heating treatment at a power of 500 W for 6 minutes to carbonize the aerogel inside the composite material to obtain a N, P co-doped porous biocarbon@In2O3 composite material with a three-dimensional structure.
[0104] Step S4: Preparation of N and P co-doped porous biocarbon@In2O3@S composite materials
[0105] The N, P co-doped porous biocarbon@In2O3 and elemental sulfur in step S3 are evenly mixed in a mass ratio of 3:7, and then the mixed material is transferred to a tubular furnace and calcined at 155°C for 6 hours under nitrogen protection to finally obtain a N, P co-doped porous biocarbon@In2O3@S composite material.
[0106] Product performance test:
[0107] Before the electrochemical test, the electrodes are prepared and button cells are assembled, and then the battery electrical performance is tested using a charge and discharge test cabinet.
[0108] like Figure 1 As shown, the mechanism diagram of the inhibition of LiPSs by the lithium-sulfur battery positive electrode material prepared in Example 1 of the present invention, the N, P co-doped porous biocarbon@In2O3@S composite material with the multifunctional coupling effect of "confinement-anchoring-catalytic conversion" realizes the confinement and anchoring of LiPSs and promotes its catalytic conversion, accelerates the catalyst to convert soluble LiPSs into insoluble discharge product Li2S, thereby inhibiting the shuttle effect of LiPSs.
[0109] from Figure 2 It can be seen from the SEM results that a three-dimensional porous biocarbon conductive network structure can be synthesized according to the method of Example 1.
[0110] from Figure 3 It can be seen from the electrical performance test results that the N, P co-doped porous biocarbon@In2O3@S composite material prepared in Example 1 of the present invention has better cycle stability performance.
[0111] Based on the above test results, it can be seen that the present invention can achieve the regulation of the microstructural properties of the positive electrode material of lithium-sulfur batteries through the key factors such as the application of environmentally friendly cross-linking agent phytic acid, the construction of three-dimensional porous biocarbon, and the loading of selective catalyst In2O3, and construct a unique lithium-sulfur battery positive electrode material with a multifunctional coupling effect of "confinement-anchoring-catalytic conversion", which effectively suppresses the shuttle effect of LiPSs. The design of the N, P co-doped porous biocarbon@In2O3@S composite material constructed in Example 1 of the present invention realizes the coupling effect of different functions: the structure not only solves the poor conductivity of sulfur, but also effectively suppresses the shuttle effect of LiPSs, and realizes the comprehensive improvement of high-rate charge and discharge performance and cycle stability performance. However, the use of a single material structure or the lack of a certain material structure (Comparative Examples 1 to 4) cannot solve the shuttle effect of LiPSs and effectively realize the improvement of electrochemical performance, and some key parameters in the preparation process cannot achieve the optimal electrochemical performance improvement effect without optimization (Examples 2 to 3).
[0112] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a positive electrode material for a lithium-sulfur battery, characterized in that The specific preparation steps are: Step S1: Preparation of porous biocarbon aerogel Dispersing chitosan in deionized water to obtain a chitosan solution with a concentration of 3wt% to 5wt%, stirring the chitosan solution in a water bath at 20 to 40°C for 1 to 3h, then adding a crosslinking agent phytic acid solution dropwise to carry out a crosslinking reaction, stopping heating and stirring after observing that chitosan and phytic acid are completely crosslinked and condensed, allowing the reaction product to stand at room temperature and then packing it into a mold, then placing it in liquid nitrogen for 5 to 20s to achieve rapid freezing, and freeze-drying it after observing that the reaction product is completely frozen to obtain a porous biocarbon aerogel; Step S2: Preparation of porous biocarbon aerogel@In2O3 composites The nano-In2O3 catalyst and anhydrous ethanol are uniformly mixed to obtain an In2O3 solution, and the porous biocarbon aerogel obtained in step S1 is immersed in the In2O3 solution, subjected to ultrasonic treatment for 1 to 3 hours, and then heated until the anhydrous ethanol is volatilized, and then freeze-dried to obtain a porous biocarbon aerogel@In2O3 composite material; Step S3: Preparation of N, P co-doped porous biocarbon@In2O3 composite material The porous biocarbon aerogel@In2O3 composite material obtained in step S2 is subjected to microwave heating treatment to carbonize the aerogel inside to obtain a N, P co-doped porous biocarbon@In2O3 composite material with a three-dimensional structure, wherein the power of the microwave heating treatment is 300-650W and the time is 2-8min; Step S4: Preparation of N and P co-doped porous biocarbon@In2O3@S composite materials The N, P co-doped porous biocarbon@In2O3 composite material obtained in step S3 is evenly mixed with elemental sulfur, and the mixed material is then transferred to a tubular furnace and calcined at 150-160° C. for 4-8 hours in an oxygen-free atmosphere to finally obtain a N, P co-doped porous biocarbon@In2O3@S composite material, i.e., a lithium-sulfur battery positive electrode material.
2. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: The concentration of phytic acid in the cross-linking agent phytic acid solution in step S1 is 0.5-1.2 mol / L.
3. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: The feeding ratio of chitosan and phytic acid in step S1 is 1g:0.5~3mL.
4. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: The freeze-drying temperature in step S1 is -80 to -50°C and the time is 8 to 72 hours.
5. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: The mass ratio of the nano-In2O3 catalyst to the porous biocarbon aerogel in step S2 is 0.5 to 3:
1.
6. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: The freeze-drying temperature in step S2 is -80 to -50°C and the time is 8 to 48 hours.
7. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: The mass ratio of the N and P co-doped porous biocarbon@In2O3 composite material to elemental sulfur in step S4 is 3:5-10.
8. Use of the lithium-sulfur battery positive electrode material prepared by the method according to any one of claims 1 to 7 in the preparation of a lithium-sulfur battery positive electrode.
9. The use according to claim 8, characterized in that: The lithium-sulfur battery positive electrode is used for assembling a lithium-sulfur battery.
Citation Information
Patent Citations
Method for preparing chitosan-based high-specific-surface-area nitrogen / phosphorus co-doped carbon nano sheet
CN108394884A
Carbon aerogel@sulfur composite material for positive electrode of lithium-sulfur battery and preparation method thereof
CN111740091A